A study on the chemical and mineral composition of the protein-mineral paste from poultry and cattle bone raw materials - A. K. Kakimov; Zh. S. Yessimbekov; B. K. Kabdylzhar; A. K. Suychinov; A. M. Baikadamova (Теория и практика переработки мяса, 2021)
When processing cattle and poultry, a large quantity of secondary slaughter products in the form of bone raw materials are formed in enterprises of the meat and poultry processing industry. Nowadays, its use is not optimal and rational. One of the promising directions of using bone raw materials in enterprises is production of finely ground meat and bone paste. The aim of this research was to study the chemical and mineral compositions, as well as the content of toxic elements in meat and bone paste from poultry and cattle bones obtained after complex grinding on a grinder and ultra-fine grinder. Chicken bone products (chicken necks, drumsticks, wings, breasts) and cattle costal and vertebral bones with residues of muscle tissue were used for investigation. The comparative analysis of the nutritional value of the meat and bone paste showed the following results: protein mass fraction was 18.5% in the meat and bone paste obtained from poultry bones, and 12.1% in the meat and bone paste obtained from cattle bones. The mass fraction of fat was two times higher in the meat and bone paste from poultry bones. As for the mineral composition, it has been established that meat and bone paste is a rich source of calcium: the calcium content was 1,654.02 mg/100g in the poultry meat and bone paste, and 5,318.13 mg/100g in the cattle meat and bone paste. In regard to the toxic element content, the normed values of lead and arsenic, cadmium and mercury were not revealed in the poultry and cattle meat and bone paste. The obtained meat and bone paste can be used for food purposes as a food additive in meat product manufacture, which will allow rational and economic use of bone raw materials in cattle and poultry processing.